Vlog-Based Assignment: A Mean of Improving PGSD Students’ Communicative Skill in Presenting Science Subject - Firdiani, Dian; Rahmat, Rahmat; Samad, Ita Sarmita (Edumaspul: Jurnal Pendidikan, 2020)
Communicative skill is important to be mastered by primary teacher candidates. The skill is required to create conducive teaching and learning process. Meanwhile, the fact shows that the students of primary school teacher (PGSD) at STKIP Muhammadiyah Enrekang have low communicative skill. Involving technology in learning is considered to be able to assist the teacher to hone the students’ communicative skill. Vlog or video blog which is technology-based can be a way to overcome the issue. The present study aims at investigating whether the use of vlog-based assignment can improve the students’ communicative skill and affect their self- confidence. Quantitative research method with quasi-experimental research design is used to complete this research. The instruments used to collect data are questionnaire and test which is arranged based on the communicative skill indicators and validated by an expert. In conclusion, the use of vlog-based assignment gives positive impact to the level of self-confidence of the students and thus enhance the students’ communicative skill as well.